PENGEMBANGAN AGROWISATA UNTUK KEMANDIRIAN EKONOMI DAN PELESTARIAN BUDAYA DI DESA KERTA, PAYANGAN GIANYAR - Gunawan, I Made (Jurnal Master Pariwisata (JUMPA); Volume 03, Nomor 01, Juli 2016DO - 10.24843/JUMPA.2016.v03.i01.p11)
Kerta Village, Payangan, Gianyar regency, Bali, has a large and diverse potential to develop as agrotourism.However, these natural and cultural potentials have not been optimally managed.This study aims to determine the potential of villages that can be developed as agrotourism products, knowing the internal and external factors that influence of agrotourism development, formulating strategy and program to develop it.This study uses qualitative methods, data collection is done through observation, questionnaires, and in-depth interviews on elements of the society, the government and tourism entrepreneurs. Qualitative descriptive analysis was performed by applying the theory of tourism area life cycle, systems theory, and planning theory.The results showed that the village potential that has been depeloping and it can be developed further as agrotourism products, grouped into four categories, namely of nature potential, agriculture, cultural, and attractions.From the view of tourism are life cycle,Kerta Village Agrotourism are in the involvement phase marked by the growing involment of community to tourism activities.
Keywords: agrotourism, Kerta Village Gianyar, tourism area life cycle, community involvement